Hatra : il territorio e l'urbanistica - Foietta, Enrico (Access archaeology., 2018)
The main purpose of the research presented in this volume has been the study of the city and the surrounding landscape of Hatra. To achieve this result, a multilayer GIS was created. It will remain an important resource for future excavations, which themselves may expand its dataset and verify it with additional ground control points.